The rehabilitation efficacy of diaphragmatic breathing combined with limb coordination training for lower limb lymphedema following gynecologic cancer surgery - Wang, Jingxin; Ma, Jiahui; Zhang, Yujie; Tian, Yuan; Wang, Xinxin; Wang, Yu; Xiang, Dongquan; Wang, Daoyu; Huang, Kun; Mao, Luxi; Zhang, Jiaxin; Fan, Huixuan; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Objective To investigate the impact of diaphragmatic breathing combined with limb training on lower limb lymphedema following surgery for gynecological cancer. Methods From January 2022 to May 2022, 60 patients with lower limb lymphedema post-gynecologic cancer surgery were chosen. They were split into a control group (n = 30) and a treatment group (n = 30). The control group underwent complex decongestive therapy (CDT) for managing lower limb lymphedema after gynecologic cancer surgery, while the treatment group received diaphragmatic breathing combined with limb coordination training alongside CDT. Both groups completed a 4-week treatment regimen. The lower limb lymphedema symptoms were evaluated using the genital, lower limb, buttock, and abdomen (GCLQ) scores; bilateral lower limb circumference measurements; and anxiety and depression scores. Results Compared to sole CDT administration, individuals undergoing diaphragmatic breathing coupled with limb coordination training experienced notable reductions in scores for the self-perceived symptom assessment questionnaire (GCLQ), bilateral lower limb circumference, as well as anxiety and depression scores. Conclusion The incorporation of diaphragmatic breathing combined withalongside limb coordination training can accelerate and augment the efficacy of treating lower limb lymphedema post-gynecologic cancer surgery.